Iradiasi Sediaan Obat Herbal Temu Putih Curcuma zedoaria (Berg) Rosc.: Cemaran Mikroba, Sitotoksisitas dan Profil Kromatogram - ERMIN KATRIN W.; EPSI NARULITA; ZUHELMI AZIZ; HENDIG WINARNO (Fakultas Farmasi Universitas Pancasila, 2013)
Gamma irradiation has been used for preservation of herbal medicines, one of which is temu putih Curcuma zedoaria (Berg) Rosc. to cure cervical cancer. This research aimed to study the gamma irradiation effects on microbial contamination, cytotoxic activity against leukemia L1210 cell lines and chromatogram profile of the temu putih active fraction. Gamma irradiation was performed with a 60Co source at 5, 7.5, 10 and 15 kGy. After irradiation at > 7.5 kGy bacteria and mould were not present on herbs. Control and irradiated samples were consecutively macerated with n-hexane, ethyl acetate and ethanol. Ethyl acetate extract was the most cytotoxic gainst L1210 leukemia cells with an IC50 value of 10.60 μg/mL as compared to n-hexane or ethanol extract. Ethyl acetate extract was fractionated with column chromatography producing six fractions. Fraction 2 was the most cytotoxic against L1210 leukemia cells with an IC50 value of 2.44 μg/mL. The thin-layer chromatographic analysis results of ethyl acetate extract and fraction 2 of control and irradiated samples showed the presence of curcumin and chromatographic pattern similar to the control. Curcumin contents in fraction 2 were between 35 to 51%, which were not significantly changed between samples, although was irradiated up to 15 kGy. The maximum dose for irradiation of temu putih herbal preparation is 15kGy.